Phytosociological and Ethanobotanical Study of Trees in a Tropical Dry Deciduous Forest in Panchmahal District of Gujarat, Western India - Pilania, P. K.; Gujar, R. V.; Joshi, P. M.; Shrivastav, S. C.; Panchal, N. S. (Indian Forester, 2015)
The present work reports the important trees from selected eleven sites of the study area in Panchmahal district of Gujarat state. Total 31 species of 22 families were recorded. The Shannon-Wiener diversity index ( Â¯H ) was 1.848, concentration of dominance (CD) 0.235, species richness 15.21 and species evenness 0.687 for the study area. Nine species are used for timber and sixteen are medicinally important. A number of species like Terminalia bellirica (Gaerth.) Roxb., Eucalyptus globulus Labill. and Boswellia serrata Roxb. Are of immense economic significance in this area which leads to low density ( 10.251, 13.258 and 17.045 trees ha-1 ) due to extreme exploitation although species like Tectona grandis L. f. and Diospyros melanoxylon Roxb.with extreme economic importance encompass high density (9558.475 and 2703.973 trees haha-1 ) due to sustainable management.